2008
DOI: 10.1200/jco.2007.13.9949
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Predictive Biomarker Profiles for Response Targeting Human Epidermal Growth Factor Receptor 2 (HER-2) in Advanced Inflammatory Breast Cancer With Lapatinib Monotherapy

Abstract: Lapatinib is well tolerated with clinical activity in heavily pretreated HER-2+, but not EGFR+/HER-2-, IBC. In this study, coexpression of pHER-2 and pHER-3 in tumors seems to predict for a favorable response to lapatinib. These findings warrant further investigation of lapatinib monotherapy or combination therapy in HER-2+ IBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(98 citation statements)
references
References 40 publications
5
92
0
1
Order By: Relevance
“…In first-line patients with trastuzumabnaïve, HER2-positive advanced or MBC, lapatinib monotherapy resulted in 24% ORR . Lapatinib combination therapy has promising efficacy as treatment for HER2-positive advanced or MBC, including treatment-naïve MBC (Geyer et al, 2006;Di Leo et al, 2008;O'Shaughnessy et al, 2008;Johnston et al, 2008a, b). The outcome of this study complements the efficacy reported earlier for lapatinib and confirms that lapatinib offers a beneficial therapeutic option to patients with HER2-overexpressing BC, including those with brain metastases.…”
Section: Discussionsupporting
confidence: 78%
“…In first-line patients with trastuzumabnaïve, HER2-positive advanced or MBC, lapatinib monotherapy resulted in 24% ORR . Lapatinib combination therapy has promising efficacy as treatment for HER2-positive advanced or MBC, including treatment-naïve MBC (Geyer et al, 2006;Di Leo et al, 2008;O'Shaughnessy et al, 2008;Johnston et al, 2008a, b). The outcome of this study complements the efficacy reported earlier for lapatinib and confirms that lapatinib offers a beneficial therapeutic option to patients with HER2-overexpressing BC, including those with brain metastases.…”
Section: Discussionsupporting
confidence: 78%
“…In fact, lapatinib was recently shown to restore endocrine sensitivity in breast cancer cells with acquired resistance because of modest adaptive upregulation of HER2 (Leary et al, 2010). Moreover, lack of p53 and phosphorylated HER3 have been associated with better lapatinib responses in HER2-overexpressing patients; HER2-overexpressing tumors also exhibit increased expression of heregulin/ neuregulin (Johnston et al, 2008). Our results for the first time link BTG2-dependent effects on cell transformation to ErbB receptor signaling, and raise the possibility that inhibition of this pathway may be relevant in the treatment of breast cancers that have reduced BTG2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…HER2 overexpression/amplification is widely accepted as a lapatinib therapy response predictor based on the results of several clinical studies 15,85,86 . Coexpression of pHER2 and pHER3 in IBC seems to predict a favorable response to lapatinib even more accurately 87 . On the other hand, HER1 did not predict lapatinib response in various studies 15,40,85,88 .…”
Section: The Her Familymentioning
confidence: 99%